Workplace Violence against Nurses in Bangalore, India - Adhikari, Laxmi (Europasian Journal of Medical Sciences, 2022)
Background Research on workplace violence in the health sector in India is emerging. This paper reports on a study on violence against nurses working in hospitals in Bangalore, India. Data and Methods A descriptive cross-sectional study was undertaken with both qualitative and quantitative approaches. The respondents were female nurses working in hospitals in Bangalore city, India. Data was collected through a self-administered questionnaire, completed during the period May–June 2017. Results Of the total 175 nurses requested, 110 (62.8%) consented to participate in the study. Over a six-month period preceding the interview, 33.6% of the respondents faced at least one type of violence. An overwhelming majority (73%) experienced only verbal violence; the rest experienced multiple forms of violence, which included verbal, physical and sexual. The factors associated with workplace violence were stressful conditions, miscommunication, excessive workload, lack of security, and working alone. The majority of the assaults were not reported. Conclusion Policies and intervention programs need to be developed toward making a work environment free of violence.